Gum arabic and red propolis protecteting colorectal preneoplastic lesions in a rat model of azoxymethane - Braga,Vanessa Nogueira Lages (2019)
Abstract Purpose: To evaluate red propolis, gum arabic and L-lysine activity on colorectal preneoplastic lesions induced by azoxymethane (AOM). Methods: The study featured 4 control groups (I-IV) and 4 experimental groups (V-VIII), totaling 48 rats. Once a week for 2 weeks, animals on control groups received saline, while animals in experimental groups received azoxymethane (15 mg/kg i.p.). The follow up along 16 weeks included daily oral gavage to administer water (I and V), L-lysine (150 mg/kg)(II and VI), própolis (100mg/5ml/kg)(III and VII), or gum arabic (5ml/kg)(IV and VIII). Was performed surgery on the animals in the end of this time in order to collect blood for biological assays (TBARS, GSH), followed by their sacrifice to tissue extract. Results: Oxidative stress (TBARS) and the number of aberrant crypt foci (ACF) in distal colon were lower using própolis (p<0.01 for both parameters). Gum arabic reduced preneoplastic lesions (ACF ≤ 4 crypts) on distal colon and on the entire colon (p<0.05). Conclusions: Red propolis reduced AOM-induced oxidative stress (TBARS) and total number of ACF in the distal colon. L-lysine neither protected against nor enhanced AOM-induced ACF. Gum arabic reduced the number of ACF.